SOCIAL COMPETENCE AND AFFECTIVE STYLES OF EMOTION REGULATION AMONG UNIVERSITY STUDENTS - Khan, Dr. Mussarat Jabeen; Gulmeena Tahir; Ajmal, Dr Fouzia (Journal of Arts & Social Sciences, 2022)
Being social animals human being always strive to interact with others, which needs social competence. However they need to manage their emotions also. This particular research was carried out to find the relationship between social competence and different affective styles of emotion regulation of university students. Moreover the gender difference on social competence and affective styles of emotion regulation was also checked. Correlation research design was used and data were collected through survey technique from male and female students of Foundation University, COMSATS University, Quaid-i-Azam University, Capital University and International Islamic University. Social Competence Scale and Affective Style Questionnaire were administered on university students for data collection which were analysed using mean, Standard Deviation, t-Test and pearson correlation. A significant correlation between social competence and affective styles of emotional regulation (adjusting, tolerating and concealing styles) was found. It was also observed that gender difference between university students on social competence was significant. However gender difference on emotional regulation was non-significant. Using positive affective styles of emotional regulation can help to reduce stress, tension, anxiety and depression among university students.